Thinking about the future Career readiness insights from national longitudinal surveys and from practice - Covacevich, Catalina (OECD Education Working Papers, 2021)
This paper explores how teenage thinking about jobs and careers relates to adulthood labour market outcomes. The OECD working paper Career Ready? How schools can better prepare young people for working life in the era of COVID-19 identifies career certainty, alignment and ambition as relevant indicators related to career thinking. This paper extends analysis of these indicators to new longitudinal datasets from Australia, Denmark, and Switzerland, and incorporates two new indicators, instrumental motivation and career concentration. The findings provide further evidence that teenage career ambition, certainty, alignment, instrumental motivation and broad occupational expectations relate to positive employment outcomes, including in periods of economic turbulence. However, this is not always the case and on some occasions, this association is found only in specific subgroups. Finally, the paper presents evidence from the academic literature, analysis of OECD PISA data and accounts from practitioners, which focus on ways in which schools can foster students' career thinking